2017
DOI: 10.1080/02640414.2017.1411867
|View full text |Cite
|
Sign up to set email alerts
|

Validity of an ultra-wideband local positioning system to measure locomotion in indoor sports

Abstract: The validity of an Ultra-wideband (UWB) positioning system was investigated during linear and change-of-direction (COD) running drills. Six recreationally-active men performed ten repetitions of four activities (walking, jogging, maximal acceleration, and 45º COD) on an indoor court. Activities were repeated twice, in the centre of the court and on the side. Participants wore a receiver tag (Clearsky T6, Catapult Sports) and two reflective markers placed on the tag to allow for comparisons with the criterion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 27 publications
3
69
1
2
Order By: Relevance
“…In the case of total distance travelled, the mean bias compared to VICON was <0.5% for both Gen4 and Gen5, which is well in line with values of 0.1-3.5% reported by previous investigations utilizing several types of GPS-, radio-, and video-based EPTS [20,21,23,[35][36][37]. Likewise, we found only trivial differences in peak speed measures for both Gen4 (1.13%) and Gen5 (0.14%), which is comparable with recent validations of four different GNSS and LPS systems (<2.1%, [38,39].…”
Section: Discussion Of Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In the case of total distance travelled, the mean bias compared to VICON was <0.5% for both Gen4 and Gen5, which is well in line with values of 0.1-3.5% reported by previous investigations utilizing several types of GPS-, radio-, and video-based EPTS [20,21,23,[35][36][37]. Likewise, we found only trivial differences in peak speed measures for both Gen4 (1.13%) and Gen5 (0.14%), which is comparable with recent validations of four different GNSS and LPS systems (<2.1%, [38,39].…”
Section: Discussion Of Resultssupporting
confidence: 89%
“…Unfortunately, however, previous research has demonstrated that the validity and reliability of high-intensity performance indicators is likely inversely related to their importance in terms of load monitoring, that is, high-speed running, acceleration/deceleration work, and metabolic power being the least valid and reliable variables [40,41]. Recent examples indeed showed deviations of 20-40% in distances travelled while running with high intensities [28,42], and up to 41% for peak decelerations during walking, and 8.9% during changes of direction [35]. In contrast to that, this study found only trivial biases in peak acceleration and deceleration values for both Gen4 and Gen5 (<0.5%) and small-to-trivial (Gen4, <10%) and trivial (Gen5, <5%) deviations in high-intensity distance metrics (comprising high-speed running and sprinting distance).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Indoor team sports also utilize indoor positioning systems (IPS), which provide continuous and real-time positional information about a person or an object in an indoor environment [21,22]. Similar GPS technology, IPS are becoming increasingly popular among team sports to track player positioning and their subsequent movements [2,22]. Previously, high costs and the required fixed installation of the system at a venue, limiting mobility of the system, had deterred the use of IPS as a primary tool for monitoring eTL.…”
Section: Introductionmentioning
confidence: 99%
“…Although vision-based motion analysis is widely applied for player monitoring, findings about validity and reliability are inconsistent due to the multitude of existing systems and their dependency upon manual intervention, quality of video footage or camera positioning (Duthie et al, 2005 ; Barris and Button, 2008 ). Permanently installed microtechnological local positioning systems are able to overcome these problems showing high values of reliability (CV <2%) and validity with reported typical errors of 1.2-9.3% for distance, speed and acceleration (Leser et al, 2014 ; Rhodes et al, 2014 ; Serpiello et al, 2017 ). However, mentionable errors were found for mean and peak deceleration (TE mean = 84%, TE peak = 20%) as well as a decrease of accuracy for actions at the side of the court (Serpiello et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Permanently installed microtechnological local positioning systems are able to overcome these problems showing high values of reliability (CV <2%) and validity with reported typical errors of 1.2-9.3% for distance, speed and acceleration (Leser et al, 2014 ; Rhodes et al, 2014 ; Serpiello et al, 2017 ). However, mentionable errors were found for mean and peak deceleration (TE mean = 84%, TE peak = 20%) as well as a decrease of accuracy for actions at the side of the court (Serpiello et al, 2017 ). Furthermore, high costs and local restrictions due to their fixed installation limit the application of local positioning systems (Hedley et al, 2010 ; Stevens et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%